2018
DOI: 10.1002/mrd.22971
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte‐activating capacity of fresh and frozen–thawed spermatids in the common marmoset (Callithrix jacchus)

Abstract: The common marmoset (Callithrix jacchus) represents a promising nonhuman primate model for the study of human diseases because of its small size, ease of handling, and availability of gene-modified animals. Here, we aimed to devise reproductive technology for marmoset spermatid injection using immature males for a possible rapid generational turnover. Spermatids at each step could be identified easily by their morphology under differential interference microscopy: thus, early round spermatids had a round nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…We have previously reported that marmoset spermatids at the late round spermatid stage or later have oocyte-activating capacity (Ogonuki et al, 2018). As expected, after injection of oocytes with late round spermatids (round spermatid injection respectively, of the oocytes were activated to form two pronuclei without any exogenous activation stimuli (Table 1).…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…We have previously reported that marmoset spermatids at the late round spermatid stage or later have oocyte-activating capacity (Ogonuki et al, 2018). As expected, after injection of oocytes with late round spermatids (round spermatid injection respectively, of the oocytes were activated to form two pronuclei without any exogenous activation stimuli (Table 1).…”
Section: Introductionsupporting
confidence: 74%
“…In this study, we obtained a normal infant following ELSI, but not ICSI, probably only because ELSI embryos developed to the morula stage in vitro before embryo transfer. However, in our previous study using a 12‐month‐old male, ICSI embryos developed into blastocysts (Ogonuki et al, ). Therefore, it is likely that ICSI may also be a practical option if young donor males possess testicular spermatozoa.…”
Section: In Vitro Development Of Embryos Following Injection With Roumentioning
confidence: 92%
See 1 more Smart Citation
“…From the perspective of reproductive physiology, non-human primates are closely related to human models; however, due to the high cost of the supply and maintenance of marmosets, a limited number of researchers are using this NHP model. Although ART studies using the marmoset model are reported, studies have been focused on the IVM of oocytes using a human IVF protocol, mainly consisting of inducing maturation using gonadotropins [9,35,36,37,38]. Nevertheless, using NHP as the model for a wider range of female reproductive diseases has arisen [39].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, cryopreservation of elongated spermatids can potentially enable the preservation of genetic material of feline species. In addition, in the common marmoset, elongated spermatids could be collected from immature male tests [24]. In cats, it is also possible to collect elongated spermatids from immature individuals.…”
Section: Discussionmentioning
confidence: 99%